Inductively powered wireless pacing via a miniature pacemaker and remote stimulation control system - Parinaz Abiri (Nature Portfolio, 2017)
Abstract Pacemakers have existed for decades as a means to restore cardiac electrical rhythms. However, lead-related complications have remained a clinical challenge. While market-released leadless devices have addressed some of the issues, their pacer-integrated batteries cause new health risks and functional limitations. Inductive power transfer enables wireless powering of bioelectronic devices; however, Specific Absorption Rate and size limitations reduce power efficiency for biomedical applications. We designed a remote-controlled system in which power requirements were significantly reduced via intermittent power transfer to control stimulation intervals. In parallel, the cardiac component was miniaturized to facilitate intravascular deployment into the anterior cardiac vein. Given size constraints, efficiency was optimal via a circular receiver coil wrapped into a half-cylinder with a meandering tail. The pacemaker was epicardially tested in a euthanized pig at 60 beats per minute, 2 V amplitude, and 1 ms pulse width, restoring mean arterial pressure from 0 to 37 mmHg. Power consumption was 1 mW at a range of > 3 cm with no misalignment and at 2 cm with 45° displacement misalignment, 45° x-axis angular misalignment, or 45° y-axis angular misalignment. Thus, we demonstrated a remote-controlled miniaturized pacing system with low power consumption, thereby providing a basis for the next generation of wireless implantable devices.